2013
DOI: 10.15663/tandc.v13i0.9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-emotional Key Competencies: Can they be measured and what do they relate to?

Abstract: . It is directed towards a professional audience and focuses on contemporary issues and research relating to curriculum pedagogy and assessment. ISSN 1174-2208 Notes for ContributorsTeachers and Curriculum welcomes:• research based papers with a maximum of 3,500 words, plus an abstract or professional summary of 150 words, and up to five keywords;• opinion pieces with a maximum of 1500 words; and• book or resource reviews with a maximum of 1000 words. FocusTeachers and Curriculum provides an avenue for the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Participants in this study were sampled from students in Years 11 and 12 who attended five state-run schools in Auckland from a range of deciles. They had completed a questionnaire (Peterson, Farruggia, Hamilton, Brown, & Elley-Brown, 2013) about the KCs and had agreed to possible followup interviews. They were selected based on a cluster analysis that identified respondents who reported low or high scores on KC clusters and to reflect a variety of ethnicities and both genders.…”
Section: Participantsmentioning
confidence: 99%
“…Participants in this study were sampled from students in Years 11 and 12 who attended five state-run schools in Auckland from a range of deciles. They had completed a questionnaire (Peterson, Farruggia, Hamilton, Brown, & Elley-Brown, 2013) about the KCs and had agreed to possible followup interviews. They were selected based on a cluster analysis that identified respondents who reported low or high scores on KC clusters and to reflect a variety of ethnicities and both genders.…”
Section: Participantsmentioning
confidence: 99%
“…Attempts have been made to develop valid and reliable 10 Faculty of Education 15 March 2022 assessments of the key competencies in New Zealand. For example, Peterson et al (2013) focused on the four socio-emotional key competencies (thinking, managing self, relating to others, participating and contributing) in the New Zealand Curriculum and found that existing psychological questionnaires could be used to identify potential assessable constructs of each key competency. However, they admitted that the simultaneous use of all scales to assess the constructs diminished the individual model measures' value.…”
Section: Assessment Of Key Competencies In New Zealandmentioning
confidence: 99%